Local injection therapy for carpal tunnel syndrome: a network meta-analysis of randomized controlled trial - Zhou, TianQi; Wu, ZhuoRao; Gou, XingYun; Xia, HaiSha; Ding, JiLin; Ai, ShuangChun (Frontiers in Pharmacology, 2023)
Objective: Clinical research has shown that local injections for carpal tunnel syndrome reduce the symptoms of patients and enhance their quality of life considerably. However, there are several therapy options, and the optimal choice of regimen remains uncertain. Therefore, we comprehensively evaluated the variations in clinical efficacy and safety of several medications for treating carpal tunnel syndrome.Methods: Computer searches of Embase, PubMed, Cochrane Library, and Web of Science databases were used to collect articles of randomized controlled trials on local injections for treating carpal tunnel syndrome from database creation till June 10, 2023. Two researchers independently screened the literature, extracted information, evaluated the risk of bias in the included studies, and performed network Meta-analysis using Stata 17.0 software. Drug efficacy was assessed using symptom severity/function and pain intensity. Surface under the cumulative ranking curve (SUCRA) ranking was used to determine the advantage of each therapy.We included 26 randomized controlled trials with 1896 wrists involving 12 interventions, such as local injections of corticosteroids, platelet-rich plasma, 5% dextrose, progesterone, and hyaluronidase. The results of the network meta-analysis showed the following: (i) symptom severity: at the 3-month follow-up, D5W combined with splinting (SUCRA = 95%) ranked first, and hyaluronidase (SUCRA = 89.6%) at 6 months; (ii) functional severity: either at the 3-month followup (SUCRA = 89.5%) or 6 months (SUCRA = 83.6%), (iii) pain intensity: 5% dextrose in water combined with splinting was the most effective at the 3-month (SUCRA = 85%) and 6-month (SUCRA = 87.6%) follow-up.Considering the combination of symptoms/function and pain intensity, combining 5% dextrose in water with splinting is probably the treatment of choice for patients with carpal tunnel syndrome. It is more effective than glucocorticoids and no adverse effects have been observed.